If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) + -5(3 + -4x) = 29 + -2x Reorder the terms: 3(-2 + x) + -5(3 + -4x) = 29 + -2x (-2 * 3 + x * 3) + -5(3 + -4x) = 29 + -2x (-6 + 3x) + -5(3 + -4x) = 29 + -2x -6 + 3x + (3 * -5 + -4x * -5) = 29 + -2x -6 + 3x + (-15 + 20x) = 29 + -2x Reorder the terms: -6 + -15 + 3x + 20x = 29 + -2x Combine like terms: -6 + -15 = -21 -21 + 3x + 20x = 29 + -2x Combine like terms: 3x + 20x = 23x -21 + 23x = 29 + -2x Solving -21 + 23x = 29 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -21 + 23x + 2x = 29 + -2x + 2x Combine like terms: 23x + 2x = 25x -21 + 25x = 29 + -2x + 2x Combine like terms: -2x + 2x = 0 -21 + 25x = 29 + 0 -21 + 25x = 29 Add '21' to each side of the equation. -21 + 21 + 25x = 29 + 21 Combine like terms: -21 + 21 = 0 0 + 25x = 29 + 21 25x = 29 + 21 Combine like terms: 29 + 21 = 50 25x = 50 Divide each side by '25'. x = 2 Simplifying x = 2
| p^2-20-8p=0 | | (-2.6)+7=7+(-2.6) | | 20+8p=p^2 | | 9b+36=b^2 | | 6-(-15)= | | 3x=15y | | (-3y^2)(2xy)(-x)= | | 16X^3-24x^2-12x-14=0 | | (-3y^2)(2xy)= | | 2*(2+2)/2= | | 8x^2=7x | | f^2=10f-16 | | a^2+8a-9=0 | | (c-6)(c-3)=23 | | 5w*u*u= | | x(x-1)=x | | a(a-5)= | | 7x-14=48-14x-28 | | 2x+4=36-2x | | 2(x-2)=3(x+3) | | 7x-3y+14=0 | | 11(4-6(40))+5(13(40)+1)=9 | | 4x^2-17x+15=-5x+10 | | -4x+12y-6=0 | | 2x+6y-8=0 | | 2x+6y-8=o | | 7-9x=47-37x | | 5x+3y+12=0 | | 2(14)=x(x+6) | | 1.05x=20 | | 14=x/12 | | 34=r/6 |